2015
DOI: 10.1038/ki.2015.147
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 inhibits cisplatin-induced acute kidney injury by modulating regulatory T cells by the CD206 mannose receptor

Abstract: Previously, we found that Foxp3-expressing CD4(+) regulatory T (Treg) cells attenuate cisplatin-induced acute kidney injury in mice and that bee venom and its constituent phospholipase A2 (PLA2) are capable of modulating Treg cells. Here we tested whether PLA2 could inhibit cisplatin-induced acute kidney injury. As a result of treatment with PLA2, the population of Treg cells was significantly increased, both in vivo and in vitro. PLA2-injected mice showed reduced levels of serum creatinine, blood urea nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 31 publications
1
79
0
Order By: Relevance
“…Furthermore, we found that PLA2 is the active compound in bee venom capable for modulating the Treg populations, both in vitro and in vivo [9,10,11]. PLA2 from bee venom belongs to group III secreted PLA2 (sPLA2) enzymes, which play important roles in a wide range of cellular functions, including phospholipid metabolism, signal transduction, and inflammatory and immune responses [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, we found that PLA2 is the active compound in bee venom capable for modulating the Treg populations, both in vitro and in vivo [9,10,11]. PLA2 from bee venom belongs to group III secreted PLA2 (sPLA2) enzymes, which play important roles in a wide range of cellular functions, including phospholipid metabolism, signal transduction, and inflammatory and immune responses [27].…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al have reported that bvPLA2 directly bound to CD206 mannose receptor on dendritic cells and induces the secretion of prostaglandin E2 (PGE2), which promotes immune tolerance through Treg differentiation via PGE2 receptor signaling and prevents the neuroinflammatory responses in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced mouse model of Parkinson’s disease [9]. In addition, anti-inflammatory effects bvPLA2 was also mediated by IL-10 secretion and Treg activation in cisplatin-induced acute kidney injury model [10]. Based on these results, we supposed that bvPAL2 could inhibit inflammatory responses by modulating Treg cells through the CD206 mannose receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several cancers, including ovarian cancer, have demonstrated resistance or reduced sensitivity to cisplatin treatment, leading to decreased time to disease progression, increased likelihood of relapse, and reduced efficacy upon re-treatment during relapse [3,4]; cisplatin itself causes significant health problems, such as nephrotoxicity [5]. Ideally, cisplatin in combination with a drug that diminishes its negative effects while enhancing the therapeutic effects would decrease resistance or relapse while mitigating its negative effects.…”
Section: Introductionmentioning
confidence: 99%